Microplastics in human samples: Recent advances, hot-spots, and analytical challenges - Malafaia, Guilherme; Barceló, Damià (TrAC, Trends in analytical chemistry (Regular ed.), 2023)
Given the rapid advancement of microplastic (MP) contamination studies, we present a comprehensive review in which the studies that identified and characterized MPs in human biological samples, indexed in consulted databases until December 23, 2022, are presented, evaluated, and discussed. Although the studies included in this review report important findings on the presence of MPs in several human biological samples, our know-how in this area still needs to be improved. Thus, we discuss in this review the hot spots and analytical and procedural challenges to be overcome, including the need to expand international collaboration networks, improve volunteer recruitment criteria, and the procedures adopted in the collection and processing stages of samples, detection, and polymeric identification of MPs. Furthermore, we reinforce the importance of adopting more adequate quality assurance/quality control (QA/QC) procedures to generate more robust and reliable data on human contamination by MPs. [Display omitted] •Current studies reveal that our knowledge about MP in humans is limited.•Establishment of collaboration networks is necessary to expand studies on the subject.•Analysis on the collection and processing of human samples is presented in this review.•QA/QC is a critical component in MP studies in human samples.•Suggestions for improving studies related to MPs in human samples are provided.